Результати вивчення інтродукованих видів роду Cerasus Mill. в умовах Лівобережного Полісся - Kirienko, S.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The results study of the four introduced species of genus Cerasus Mill: С. avium (L.) Moench., C. besseyі Baіley., С. tomentosa (Thunb.) Wall. С. vulgаrіs L. in conditions of Left-Bank of Polissya are represented. Their morphological, biological, ecological parti cularities, seasonal rhythm of development are described. It is also determined that the plants in conditions of Left-Bank of Polissya go thorough the com plete cycle of development and are perspective for decorative plantation of towns.